Pomoże ktoś ?
Potrzebuje na teraz

Odpowiedź:
[tex]6. - (3x - y) + (2x + 3y) = - 3x + y + 2x + 3y = - x + 4y \\ (a + 3b) - (7b - 4a) = a + 3b - 7b + 4a = 5a - 4b \\ - ( - 2k - 3) - ( - 7 + 5k - {k}^{2} ) = 2k + 3 + 7 - 5k + {k}^{2} = - 3k + 10 + {k}^{2} \\ - (3 - 4x) + (x - 1) - (2x - 9) = - 3 + 4x + x - 1 - 2x + 9 = 5 + 3x[/tex]
Odpowiedź:
- ( 3x-y) + ( 2x+3y)= -3x +y +2x +3y= -x +4y
( a+3b ) - ( 7b-4a)= a + 3b -7b +4a= 5a -4b
- ( - 2k-3) - ( -7 +5k - k²)= 2k +3 +7 -5k +k²= k²-3k +10
- ( 3-4x) + ( x-1) - ( 2x-9)= -3 +4x +x-1 -2x +9= 3x+5
Szczegółowe wyjaśnienie: